Integrating Body Engineering Principles in Postoperative ACL Rehabilitation for Functional Recovery: A Literature Review (The International Journal for Scientific Research, 2026)
Anterior cruciate ligament reconstruction (ACLR) rehabilitation is a multifactorial process that requires the integration of strength restoration, neuromuscular control, biomechanical symmetry, and objective return-to-sport criteria to achieve optimal functional recovery. Contemporary evidence supports criteria-based progression over purely time-based protocols, emphasizing performance-based decision-making to reduce reinjury risk and enhance long-term outcomes. However, variability persists in the implementation of rehabilitation progression models, biomechanical load management, and functional benchmarking strategies. This literature review synthesizes current evidence on postoperative ACLR rehabilitation and explores the theoretical integration of Body Engineering (BE) principles as a structured conceptual framework. BE conceptualizes rehabilitation as a dynamic systems process that systematically integrates biomechanical, physiological, and functional parameters into individualized progression pathways. By emphasizing objective assessment, load calibration, and functional symmetry restoration, this approach may enhance clinical decision-making and optimize recovery trajectories. Further empirical research is required to validate the clinical applicability and effectiveness of Body Engineering principles within standardized ACLR rehabilitation programs.
Keywords: Anterior cruciate ligament reconstruction; ACL rehabilitation; Body Engineering; criteria-based progression; return to sport; neuromuscular control; functional recovery; biomechanical symmetry